Monthly Occurrence, Maturation Time and Some Host Factor Effects on the Spirurine Nematode Rhabdochona (Rhabdochona) longispicula Belous, 1965 Parasitizing Cyprinion macrostomus (Ostiechthyes: Cyprinidae) From Greater Zab River - Samir Jawdat Bilal (Polytechnic Journal)
Samples of the native fish Cyprinion macrostomus were collected monthly from three different points of Greater Zab River (Rezan, Qandil and Aski-kalak), from January to the end of December 2022. The goals of this study was to determine the prevalence, mean intensity and abundance of infected C. macrostomus with Rhabdochona (Rhabdochona) longispicula, the time and rate of parasite maturation, time of higher peak/ lower appearance of infection were studied. On other hand, effects of some host factors like sex and age were also revealed. The study showed fishes infections with the nematode Rhabdochona longispicula with a highest prevalence (42.85%) of infection, highest mean intensity (3.80) and highest abundance (0.95). The time and rate of maturation, time of higher peak/ lower appearance of infection. On other hand, effects of some host factors like sex and age were revealed also. The peak infection was noticed in May-June (maximum peak in June, prevalence= 42.85), while the least infections noticed in January-February (minimum peak in February, prevalence= 5.26). The fully matured nematodes (males and gravid females) were seen for first time in the end of May to the end of July (highest in July 8 fish specimens with mature parasites); even it is continuing to August but in lower numbers (2 fish specimens with mature parasites). About host factors, non-significant differences of infection rate were found between male and female fish host, while direct proportions of the age (length) of fishes with prevalence, mean intensity and abundance of R. longispicula were recorded. From previous results, it can be concluding that host sex have no significant effects on nematodes infection, while the host age has significance effects, as well as the maturation time is strongly relate to the year months that indicate the environmental effects on it.